Shear Behavior of Joint The Partial Prestressed Concrete Beam-Column Reinforced Concrete of Ductile Frame Structure Building In a Scure Residents and for Settlement Environment - Made D Astawa; IGP Raka; Tavio Tavio (Institut Teknologi Sepuluh Nopember, 2014)
Concentration of this study is to create a Specimens model of Joint Interior Beam - Column using Partial Prestressed Concrete Beams elements connected with Reinforced Concrete Column. Design capacity of Beam- Column Joint Shear is the horizontal shear reinforcement in the form of stirrups Æ 10-50 mm to fill the empty space bj = 288 mm . The capacity Shear that can be deployed by the cross bar = 103.62 kN. Total shear force that is capable of detained by the beam-column joint structures are Vjh = 409 kN. This study is a continuation of research SRPMK models shaped beam - column joint with beam section 250/400 mm , and the column section 400/400 mm , the source of funds from Research Ditlitabmas Decentralization Program of Higher Education , through ITS Featured Research Grant in 2013 . Experimental studies have been conducted with Cyclic loading ( pseudo dynamic ) lateral , static axial load on the column as a stabilizer . Specimens ability to withstand Ultimate Lateral Cyclic Load : conditions Load push (press) = 470.90 kN and Load Pull = 465.80 kN. Everything is > 409 kN.Ductility structure also qualified in 3.50% Drift Ratio: Conditions Press m = 1.27 > 1.20, Pull Conditions m = 1.29 > 1.20. In general, behavioral modeling structure has qualified as a reliable protection occupancy when the building was hit by an earthquake.